Physiological effects of adding ECCO(2)R to invasive mechanical ventilation for COPD exacerbations - Diehl, J.-L. (Ann Intensive Care, 2020)
BACKGROUND: Extracorporeal CO(2) removal (ECCO(2)R) could be a valuable additional modality for invasive mechanical ventilation (IMV) in COPD patients suffering from severe acute exacerbation (AE). We aimed to evaluate in such patients the effects of a low-to-middle extracorporeal blood flow device on both gas exchanges and dynamic hyperinflation, as well as on work of breathing (WOB) during the IMV weaning process. STUDY DESIGN AND METHODS: Open prospective interventional study in 12 deeply sedated IMV AE-COPD patients studied before and after ECCO(2)R initiation. Gas exchange and dynamic hyperinflation were compared after stabilization without and with ECCO(2)R (Hemolung, Alung, Pittsburgh, USA) combined with a specific adjustment algorithm of the respiratory rate (RR) designed to improve arterial pH. When possible, WOB with and without ECCO(2)R was measured at the end of the weaning process. Due to study size, results are expressed as median (IQR) and a non-parametric approach was adopted. RESULTS: An improvement in PaCO(2), from 68 (63; 76) to 49 (46; 55) mmHg, p = 0.0005, and in pH, from 7.25 (7.23; 7.29) to 7.35 (7.32; 7.40), p = 0.0005, was observed after ECCO(2)R initiation and adjustment of respiratory rate, while intrinsic PEEP and Functional Residual Capacity remained unchanged, from 9.0 (7.0; 10.0) to 8.0 (5.0; 9.0) cmH(2)O and from 3604 (2631; 4850) to 3338 (2633; 4848) mL, p = 0.1191 and p = 0.3013, respectively. WOB measurements were possible in 5 patients, indicating near-significant higher values after stopping ECCO(2)R: 11.7 (7.5; 15.0) versus 22.6 (13.9; 34.7) Joules/min., p = 0.0625 and 1.1 (0.8; 1.4) versus 1.5 (0.9; 2.8) Joules/L, p = 0.0625. Three patients died in-ICU. Other patients were successfully hospital-discharged. CONCLUSIONS: Using a formalized protocol of RR adjustment, ECCO(2)R permitted to effectively improve pH and diminish PaCO(2) at the early phase of IMV in 12 AE-COPD patients, but not to diminish dynamic hyperinflation in the whole group. A trend toward a decrease in WOB was also observed during the weaning process. Trial registration ClinicalTrials.gov: Identifier: NCT02586948.